2018
DOI: 10.1016/j.jnutbio.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 and omega-6 polyunsaturated fatty acids modulate hepatic pathology

Abstract: Recent evidence has suggested that dietary polyunsaturated fatty acids (PUFAs) modulate inflammation; however, few studies have focused on the pathobiology of PUFA using isocaloric and isolipidic diets and it is unclear if the associated pathologies are due to dietary PUFA composition, lipid metabolism or obesity, as most studies compare diets fed ad libitum. Our studies used isocaloric and isolipidic liquid diets (35% of calories from fat), with differing compositions of omega (ω)-6 or long chain (Lc) ω-3 PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 73 publications
1
33
0
1
Order By: Relevance
“…The contents of DHA and EPA in the serum and liver tissue of DHA/EPA-treated mice were notably increased in our study. It is also well known that dietary fat, including DHA and EPA, alters the FA composition of various organs [ 12 , 18 ]. Our results showed that the increased MUFAs and decreased SFAs, n-6 PUFAs, and n-3 PUFAs with an increase of the n-6/n-3 ratio were observed in liver tissue of HFD-fed mice compared to that in the ND-fed mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contents of DHA and EPA in the serum and liver tissue of DHA/EPA-treated mice were notably increased in our study. It is also well known that dietary fat, including DHA and EPA, alters the FA composition of various organs [ 12 , 18 ]. Our results showed that the increased MUFAs and decreased SFAs, n-6 PUFAs, and n-3 PUFAs with an increase of the n-6/n-3 ratio were observed in liver tissue of HFD-fed mice compared to that in the ND-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of different dietary n-6/n-3 ratio on health and disease have drawn close attention. A higher intake of n-6 FA and higher dietary n-6/n-3 FA ratio were reported in NAFLD subjects [ 18 ]. On the other hand, additional evidence also highlighted the role of ratios of DHA and EPA in the prevention and treatment of chronic disease in rat models [ 19 22 ], indicating the importance of both n-6/n-3 ratios and DHA/EPA ratios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that high levels of PUFAs and a high ω‐6/ω‐3 ratio in PN may contribute to increased incidence of cholestasis, steatosis, sepsis, changes in neutrophil function, and upregulation of matrix metalloproteinases (MMPs) . The ω‐6 PUFA arachidonic acid (AA) produces prostaglandins (PGs), thromboxanes (TXs), 5‐hydroxy‐eicosatetraenoic acid, and other 4‐series leukotrienes (LTs) that are proinflammatory . The ω‐3 fatty acid eicosapentaenoic acid (EPA) produces 3‐series PGs, TXs, and 5‐series LTs, which have less detrimental effect than AA‐derived mediators have …”
Section: The Role Of Lipidsmentioning
confidence: 99%
“…The liver is an important organ for PUFA synthesis . It also benefits from omega‐3 PUFAs by decreased incidence of nonalcoholic fatty liver disease, less apoptotic hepatocytes, increased glycogen storage, and lower hepatic triacylglycerol secretion . High CER levels on the other hand may favor the development of nonalcoholic fatty liver disease, apoptosis, and lipogenesis in liver .…”
Section: Introductionmentioning
confidence: 99%